MEMAHAMI PEMELIHARAAN ALLAH DALAM BENCANA GAGAL PANEN DI DAERAH SA’DAN TIROALLO BERDASARKAN MODEL BERTEOLOGI KOSUKE KOYAMA - jimmi Pindan Pute; Lidia Rante Bua; Naomi Sampe (Phronesis: Jurnal Teologi dan Misi, 2024)
Recognition of God's love and care is not enough through fellowship but also through disasters in life, one of which is crop failure. This research aims to discover and understand the form of God's providence through crop failure disasters based on God's will, which is present in human life. Several theories used by the author include disaster theory, Kosuke Koyama's theology, and theories about God, which several authors have summarized. The research method used by the author is qualitative with a descriptive approach. Qualitative was developed through a literature study sourced from relevant book literature, articles and internet sources. To complete this article, the author used an analysis method in the form of interviews. The research results from this article show that the disaster of crop failure did not occur because of God's hatred but rather as a form of care so that humanity turns to Him and lives in a movement of ecumenical love for others. Based on Kosuke Koyama's theory, it can be concluded that God's intention for the crop failure disaster that occurred in the Sa'dan Tiroallo area was as a form of invitation so that humans have concern in terms of love for their neighbours, as well as a form of warning so that people can spend time communing with God and to repent and turn to God.